2013
DOI: 10.1175/jcli-d-11-00676.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sensitivity of the Weather Research and Forecasting Model to Parameterization Schemes for Regional Climates of Europe over the Period 1990–95

Abstract: The Weather Research and Forecasting model (WRF) is used to downscale interim ECMWF Re-Analysis (ERA-Interim) data for the climate over Europe for the period 1990-95 with grid spacing of 0.448 for 12 combinations of physical parameterizations. Two longwave radiation schemes, two land surface models (LSMs), two microphysics schemes, and two planetary boundary layer (PBL) schemes have been investigated while the remaining physics schemes were unchanged. WRF simulations are compared with Ensemble-Based Prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 37 publications
9
86
0
Order By: Relevance
“…Similar findings are reported by Kryza et al [43] for the area of Poland, where the air temperature bias is low in winter (mean bias -0.6 K), but where summer temperatures are significantly overestimated (up to +1.0 K). A bias in WRFcalculated air temperatures were also reported by Mooney et al [44] and Miglietta et al [37]. The model performs well at simulating wind speed for Europe, with mean bias not exceeding 0.5 m s-1 [37,[45][46][47], which is the second variable affecting ammonia emissions in this study.…”
Section: The Wrf-chem Modelsupporting
confidence: 87%
“…Similar findings are reported by Kryza et al [43] for the area of Poland, where the air temperature bias is low in winter (mean bias -0.6 K), but where summer temperatures are significantly overestimated (up to +1.0 K). A bias in WRFcalculated air temperatures were also reported by Mooney et al [44] and Miglietta et al [37]. The model performs well at simulating wind speed for Europe, with mean bias not exceeding 0.5 m s-1 [37,[45][46][47], which is the second variable affecting ammonia emissions in this study.…”
Section: The Wrf-chem Modelsupporting
confidence: 87%
“…This indicates a contribution of the model-specific method to reduce simulated surface pressure to mean sea level, and the pronounced biases in the mentioned regions should not be overinterpreted. Still, the underestimation of mean sea-level pressure by several hectopascal over large parts of continental Europe particularly in wintertime seems to be a robust feature of the WRF experiments and is also described by Mooney et al (2013) in a sensitivity study of WRF in Europe.…”
Section: Spatial Bias Patternmentioning
confidence: 83%
“…The fact that the temperature bias range of the three WRF-11 experiments often corresponds to the bias range of the entire ensemble illustrates the uncertainty introduced by the choice of parameterizations and parameter settings (e.g., Bellprat et al, 2012a;Mooney et al, 2013). This, however, is not apparent for precipitation biases where the different WRF setups approximately agree on sign and magnitude of their bias.…”
Section: The Overall Picturementioning
confidence: 97%
“…A complete description of the WRF multiphysics ensemble used in this study can be found in Mooney et al (2013), and only a brief summary is included here for completeness. The ensemble consists of thirteen WRF simulations driven by ERA-Interim (Dee et al 2011) over the period 1989-1995.…”
Section: Modelled Datamentioning
confidence: 99%
“…The computational cost of such a high resolution over a large domain for an extended period when several parameterizations are being investigated is difficult to justify. As discussed in Mooney et al (2013), the model is allowed to spin up for 1 year and the period covering 1990-1995 is used in the analysis. Table 1 summarises the parameterizations used in each of the 13 simulations.…”
Section: Modelled Datamentioning
confidence: 99%